PERANCANGAN SISTEM CERDAS PERAWATAN TANAMAN BERBASIS ARDUINO - Irwan Yusti; Veni Wedyawati; Asep Neris Bachtiar; Iskandar Iskandar (Sekolah Tinggi Teknologi Industri Padang, 2022)
The use of appropriate technology can reduce production costs, the use of drip irrigation systems or irrigation systems using sprinklers can help farmers maintain soil moisture but requires human intervention to operate them. Therefore, this study aims to develop an irrigation system using sprinklers that can work automatically so that it can save time and human effort. This system is an intelligent system controlled by a microcontroller so that it can work continuously with little human assistance. With this system, the plant care process can be carried out more optimally, saving water, time, energy and costs. This research is an applied research by thinking about the required infrastructure (hardware, software and human resource tools), then making a drawing design with a recycling cycle technique consisting of needs analysis, design, implementation, testing and evaluation. Needs analysis is needed to see what is needed by the system so that it can work as desired, making schematic drawings, testing the design on a simulation program (Proteus). Then at the time of implementation, the components are installed according to the schematic drawings. Finally, at the testing stage, the system performance test is carried out by conducting an evaluation stage.